Sources in science: who can we trust? - Wilkie T; Wilkie, T (Lancet, 1996)
Journalists' sources of medical and scientific news seem limitless--journals, press releases, press conferences, newsletters, scientific meetings, and "tipoffs". But whether any one piece of information satisfies two important criteria-journalistic interest and scientific credibility-is another matter. Peer-reviewed journals, in particular, are perceived to be trustworthy sources. Yet, there are increasing concerns in scientific publishing about commercial pressures from pharmaceutical companies, honorary authorship, scientific error, and outright fraud, which journalists cannot be expected to detect. That is down to the scientific community, which must recognise the importance of maintaining impartial sources of public information.